Silk gland-specific tRNA(Ala) genes interact more weakly than constitutive tRNA(Ala) genes with silkworm TFIIIB and polymerase III fractions. - Sullivan, H S (1994)
Constitutive and silk gland-specific tRNA(Ala) genes from silkworms have very different transcriptional properties in vitro. Typically, the constitutive type, which encodes tRNA(AlaC), directs transcription much more efficiently than does the silk gland-specific type, which encodes tRNA(AlaSG). We think that the inefficiency of the tRNA(AlaCG) gene underlies its capacity to be turned off in non-silk gland cells. An economical model is that the tRNA(AlaSG) promoter interacts poorly, relative to the tRNA(AlaC) promoter, with one or more components of the basal transcription machinery. As a consequence, the tRNA(AlaSG) gene directs the formation of fewer transcription complexes or of complexes with reduced cycling ability. Here we show that the difference in the number of active transcription complexes accounts for the difference in tRNA(AlaC) and tRNA(AlaSG) transcription rates. To determine whether a particular component of the silkworm transcription machinery is responsible for reduced complex formation on the tRNA(AlaSG) gene, we measured competition by templates for defined fractions of this machinery. We find that the tRNA(AlaSG) gene is greatly impaired, in comparison with the tRNA(AlaC) gene, in competition for either TFIIIB or RNA polymerase III. Competition for each of these fractions is also strongly influenced by the nature of the 5' flanking sequence, the promoter element responsible for the distinctive transcriptional properties of tRNA(AlaSG) and tRNA(AlaC) genes. These results suggest that differential interaction with TFIIIB or RNA polymerase III is a critical functional distinction between these genes.